Faktor-Faktor yang Mempengaruhi Pendapatan Petani Pinang Di Kecamatan Mendahara Tanjung Jabung Timur - Saknaria Saknaria (Universitas Batanghari Jambi, 2020)
This study aims to determine the effect of variable land area, the amount of production, the price of palm variable costs, labor and income. It is known that the price of areca nuts tends to be high. Areca prices in the village of Bhakti are ideal, and the lowest sait prices are merbau and the lowest price of areca nuts is Lagan Ilir village, with 2,836 in 2017 ha. And the smallest land area in the village of base of thorns, This study uses Primary data in 2018. The method used in this study is the method of multiple linear regression. Done to identify variables that affect the income of areca nut farmers. The value obtained turns out that the f-calculated value is greater than the f-table value means that the area of land, the amount of production, the price of areca nuts, variable costs and labor have a significant effect on the income of the areca nut farmers in Mendahara District, Tanjung Jabung Timur Regency. Land area, amount of production, areca prices, variable costs and labor have a significant effect on the income of areca farmers in Menahara Subdistrict Tanjung Jabung Timur. The wide influence of areca nut on the income of the areca nut farmers in the amount of production does not have a significant effect on the income of the areca nut farmers in Mendahara Subdistrict Tanjung Jabung Timur. The effect of the amount of production on the income of the areca nut farmers in the amount of production does not significantly influence the income of the areca nut farmers in Tanjung Jabung Timur District. Effect of areca nut prices on areca nut farmers income has no significant effect on areca nut farmers' income in Mendahara Subdistrict Tanjung Jabung Timur. Effect of variable costs on areca farmers 'income Variable costs do not have a significant effect on areca farmers' income in Tanjung Jabung Timur District. The effect of labor on areca nut farmers 'income does not have a significant effect on the areca nut farmers' income in Tanjung Jabung Timur District.